Damage spreading and coupling in spin glasses and hard spheres - Hukushima, Koji; Krauth, Werner (Frontiers in Physics, 2025)
We study the connection between damage spreading, a phenomenon long discussed in the physics literature, and the coupling of Markov chains, a technique used to bound the mixing time. We discuss in parallel the Edwards–Anderson spin-glass model and the hard-disk system, focusing on how coupling provides bounds on the extension of the paramagnetic and liquid phases. We also work out the connection between path coupling and damage spreading. Numerically, the scaling analysis of the mean coupling time determines a critical point between fast and slow couplings. The exact relationship between fast coupling and disordered phases has not been established rigorously, but we suggest that it will ultimately enhance our understanding of phase behavior in disordered systems.